Fabrication of Eco-friendly UV-visible Driven Ni:CaCO3 Photocatalyst for Sustainable Environmental Remediation - Ramasamy, V.; Sathishpriya, T.; Thenpandiyan, E.; Suresh, G. (Asian Journal of Chemistry, 2023)
Nano CaCO3, polymethyl methacrylate (PMMA) decorated Ni-doped CaCO3 nanoparticles (CPN) were synthesized from natural calcium magnesium carbonate (CaMg(CO3)2) via biomimetic synthetic route. The obtained products were thoroughly characterized through various physico-chemical techniques such as UV-DRS, PL, FTIR, XRD, TG-DTA, FE-SEM with EDX mapping, HR-TEM and SAED patterns. The XRD results revealed that the prepared products were in pure rhombohedral structure with the size range of 20-50 nm, respectively. Compared to other synthesized products, the sample CPN6 exhibited a blue-shifted band gap (2.7 eV) and red-shifted absorption and emission values. The morphological analysis of the samples shows the aggregated and rhombohedral with high porous like structure. The TG-DTA analysis shows the good thermal stability (up to 830 ºC). The photocatalytic activity exhibits a higher degradation efficiency 87% and 97% against methylene blue and rhodamine B dyes, respectively. The effect of different scavenger agents (ascorbic acid, AgNO3, EDTA2NA and isopropanol acid) was used to examine the efficiency of the photocatalytic activity. Based on the results, the prepared CPN6 nanoparticles show a great potential candidate for removal of organic dyes in the aqueous medium.